Predictors and prognosis of elderly hip fracture patients with perioperative atrial fibrillation: a nested case–control study - Wei Li; Aoying Min; Wei Zhao; Weining Li; Shuhan Li; Saidi Ran; Mingming Fu; Qili Yu; Junkai Kou; Zhiqian Wang; Zhiyong Hou (BMC Geriatrics)
Abstract Background A scarcity of data exists concerning atrial fibrillation (AF) during the perioperative stage of non-cardiothoracic surgery, particularly orthopedic surgery. In addition, given the frequency and significant impact of AF in the perioperative period, therefore our aim was to identify prognosis and predictors of elderly hip fracture patients with perioperative AF. Methods An examination of hip fracture patients at the Third Hospital of Hebei Medical University, who had been hospitalized from January 2018 to October 2020 in succession, was conducted retrospectively. To determine independent risk factors for paroxysmal AF in elderly hip fracture patients, univariate and multivariate logistic regression analysis were employed. The Kaplan–Meier survival curve demonstrated the correlation between all-cause mortality in the non-AF, paroxysmal AF, and permanent AF groups. An assessment of the correlation between baseline factors, complications, and all-cause mortality was conducted through univariable and multivariable Cox proportional hazards analysis. Results Enrolling 1,376 elderly patients with hip fractures, we found 1,189 in the non-AF group, 103 in the paroxysmal AF group, and 84 in the permanent AF group. Kaplan–Meier survival curves revealed a significantly lower overall survival rate in elderly hip fracture patients with AF, especially permanent AF. Based on COX regression analysis, we found that the main risk factors for all-cause death in elderly hip fracture patients with AF were concomitant pulmonary infection(HR 2.006,95%CI 1.019–3.949, P = 0.044), hyponatremia(HR 2.417,95%CI 1.177–4.961, P = 0.016), permanent AF(HR 2.806, 95%CI 1.036–4.198, P = 0.039). Independent risk factors for perioperative paroxysmal AF in elderly hip fracture patients were hypertension(OR 2.248, 95% CI 1.415–3.571, P = 0.001), COPD(OR 4.694, 95% CI 2.207–9.980, P < 0.001) and ACCI(OR 1.436, 95%CI 1.072–1.924, P = 0.015). Conclusions The mortality risk is high in elderly patients with hip fractures combined with AF. The independent risk factors for their death include permanent AF, pulmonary infection and hyponatremia. The independent risk factors for perioperative paroxysmal AF in elderly patients with hip fractures are ACCI, hypertension and COPD. we should identify risk factors and optimize the treatment plan at an early stage.